Risk factors and clinicopathological finding of effusive-form feline infectious peritonitis at University Veterinary Hospital, Universiti Putra Malaysia - Chan, Jia Xin; Abdullah, Rasedee; Watanabe, Malaika; Omar, Mohamed Ariff (2012)
A retrospective study on the prevalence of effusive feline infectious peritonitis (FIP) cases at the University Veterinary Hospital, Universiti Putra Malaysia (UVH-UPM) from 2009 to 2011 was conducted. Data regarding patient signalment, history of risk factors, clinical and laboratory profiles were recorded. Eighty-three cases of suspected effusive FIP were diagnosed in UVH-UPM during that period. The study showed that 87.7% cases of effusive FIP occurred in cat less than 3 years old, 60.2% in intact male, 86.4% in Domestic Short Hair, 79.2% in cats from multi-cat household, 40.3% were in cats kept indoor and 46.8% were in those kept outdoor. Multi-cat household was a risk factor for effusive FIP. The most commonly reported clinical findings were abdominal distension, dyspnea, weight loss, jaundice, ascites and pleural effusion. The clinicopathological findings associated with effusive FIP were hyperglobulinaemia, decreased A:G ratio (<0.4), hypoalbuminaemia, hyperproteinaemia, hyperbilirubinaemia and non-regenerative anaemia. The abdominal or pleural fluid was typically exudate and modified transudate.